Genotyping-by-sequencing provides the discriminating power to investigate the subspecies of Daucus carota (Apiaceae) - Arbizu, CI (2016)
This work is supported by the USDA Agricultural Research Service. C. Arbizu is partly funded by the National Council of Science and Technology of Perú (Concytec).